ASOSIASI KETERJADIAN KOLONI VERTICILLIUM DAN INTENSITAS NAUNGAN SERTA LETAK DAUN KOPI - Subli Mujim, Rudi Ruswandi, Cipta Ginting, dan Rusdi Evizal . (Universitas Lampung, 2005)
Association of Verticillium colony intensity and shade and coffee leaf position. Since conventional control methods of leaf rust of coffee is still unsatisfactory, it is needed to study toward the possibility of using biocontrol agents including factors that may influence the occurrence of the agents. The objective of this study was to determine the strength of the association of Verticillium colony occurrence and shade and leaf position. Leaf samples were taken from four sites at three coffee fields at Sumberjaya Sub district, West Lampung. Samples were taken from plants with and without shade. From each shade level, leaves showing symptoms were taken from the plants and from the ground (fallen leaves). The samples were placed individually on plastic bag and transported to the laboratory, where the samples were incubated for four days at room temperature. The proportion of lesion caused by H. vastatrix on coffee leaves that showed whitish Verticillium colonies was recorded and modified to score 0 (without Verticillium colony) to 4 (colony 50% or more). Data were analyzed with log linear saturated model. Data suggested that the occurrence of Verticillium colony was higher on plant with canopy compared to that on plants without canopy. In addition, Verticillium occurred more frequently on leaves still on the plants compared to that on leaves on the ground. Canopy factor was relatively stronger than leaf position factor in influencing the occurrence of Verticillium colony.